Developmental Assets in Adolescent Basketball Players: Influence of Age, Maturation, Size and Functional Capacities - Kós, Luísa Duarte (2019)
Sports participation has been referred as having important influence in positive youth development (PYD) in many life-long aspects, as social, physical, physiological and intellectual components. The aim of this study was to verify influences of body size, growth-related changes and age in developmental assets. This cross-sectional design study considered 45 male adolescent basketball players aged 13.6 ± 1.5 years. Participants were engaged in a club structured training program and competed at state level competition, supervised by the Federação Paulista de Basketball (São Paulo´s state basketball Federation). There was substantial variation between athletes for all variables. Inspection of credible intervals showed a substantial variation in body size and functional capacity indicators between players grouped by age group and by maturity status. However, substantial variation by both age group or maturity status was present for DAP dimensions. No relation was observed between DAP dimensions with body size and functional capacity, partitioning the substantial variation between players by age group and maturity status. In the present study there was no substantial variation in developmental assets of adolescent basketball players by age or estimated maturity status. Also, from a multidimensional perspective, there was no influence of body dimensions and functional capacities with developmental assets.